Sort by

- Relevance
- |Time

Hint: http://nptel.iitm.ac.in/courses/IIT-MADRAS/Hydraulics/pdfs/Unit38/38_1.pdf http://www.scribd.com/doc/6554968/7708DC10620677#fullscreen:on Remember that up-stream and down-stream velocity are different.

1 Answers · Science & Mathematics · 10/05/2010

To show it to be true for n = k + 1, you have the left hand side equal to 1^2 + 2^2 + ... + k^2 + (k+1)^2 Subbing your assumption for it being true for n = k gives k(k+1)(2k+1)/6 + (k+1)^2 Then the algebra goes as follows: = [k(k+1)(2k+1)/6] + k² + 2k + 1...

1 Answers · Science & Mathematics · 07/11/2011

(1/5)*ln[abs(y - 2)] - (1/5)*ln[abs(y + 3)] = x + c I couldn't get a solution closed form but I got this: for Y=< -3 or Y => 2 Y = {2 + 3*e^[5*(x + c)]}/{1 - e^[5*(x + c)]} for -3 =< Y =< 2...

1 Answers · Science & Mathematics · 20/11/2012

Hooke's Law for isotropic materials http://www.efunda.com/formulae/solid_mechanics/mat_mechanics/hooke_isotropic.cfm

2 Answers · Science & Mathematics · 07/11/2013

TS is a product. Taking the derivative, using the product rule, d(TS) = T*d(S) + S*d(T) if d(TS) = T*d(S) , then S*d(T) must be zero, e.g. T is a constant hth http://www.answers.com/topic/product...

2 Answers · Science & Mathematics · 12/04/2011